(untitled) (Journal of Asian Development Studies, 2019)
This study examines the relationship between debt and inequality in a penal of seven South Asian economies over the period from 1996 to 2014. The study incorporated domestic debt, external debt and debt servicing as debt measures in a single penal model. The control variables are government effectiveness, GDP and trade openness. The study used Least Square Dummy Variable (LSDV) Fixed Effect model, Pooled OLS and Random Effect model with standard diagnostics of Hausman test, Langragian Multiplier test and F-test for model efficiency. The econometric analysis is also supported by standard diagnostic test for serial autocorrelation, heteroskdasticity and multicolinearity. The study determines that public debt and debt servicing are significant determinants of inequality, increase in domestic debt, external debt and debt servicing leads to decrease inequality. The study concludes that the policy authorities should conceder the importance of redistribution channel and the public debt to reduce inequality in South Asia.